Equivalence and endothelial safety of temporary intracoronary shunt device: Insights from preclinical porcine and rabbit models - Qi Chen; Yinfen Wang; Liuhuan Huang; Bin Li; Zhuo Chen; Ping Liu; Xin Jiang (PLoS ONE, 2025)
Background This preclinical investigation evaluated the operational equivalence of a temporary intracoronary shunt (TICS) device while documenting patterns of endothelial repair during the perioperative period. Methods Porcine coronary bypass models were established using off-pump (OPCAB) and on-pump beating-heart surgical approaches. Through a triple randomization design, test devices and predicate counterparts were deployed in left/right coronary arteries. Equivalence was determined at postoperative day 7 through tripartite analysis: 1) sequential laboratory measurements (preoperative to 7-day follow-up), 2) histopathological evaluation of vascular specimens, and 3) angiographic assessment. Extreme-sized device validation employed rabbit carotid arteries (small-caliber vascular bed) and abdominal aortae (large-caliber model), with equivalence criteria encompassing hemodynamic stability (flow velocity, trans-device pressure differentials) and microarchitectural preservation (endothelial integrity, internal elastic lamina continuity). Results In the conventional device cohort (12 target vessels), no perioperative type 5 myocardial infarction occurred. Postoperative CTA confirmed patent lumens and unobstructed distal flow in all vessels. Cardiac biomarkers (troponin, CK-MB, myoglobin) showed no significant differences at preoperative, 4h, 8h, 24h, 72h, or 7-day timepoints (P ≥ 0.05). For extreme-sized devices, hemodynamic parameters (mean proximal/distal pressure: test vs. predicate, P ≥ 0.05) and endothelial outcomes, including elastic lamina injury scores, demonstrated equivalence between test and predicate devices. Conclusion Functional parity between TICS and predicate devices was established in both porcine and lagomorph models, with observed endothelial alterations demonstrating transient characteristics limited to the acute perioperative window.